A shift in the balance of T17 and Treg cells in menstrual blood of women with unexplained recurrent spontaneous abortion. (August 2016) - Hosseini, Samira; Shokri, Fazel; Ansari Pour, Soheila; Jeddi-Tehrani, Mahmood; Nikoo, Shohreh; Yousefi, Mehdi; Zarnani, Amir-Hassan
Highlights: T cell subsets in MB vs. PB of fertile, URSA and infertile women. Lower frequency of MB TCRγd +, T17 cells and T17:Treg ratio in MB of URSA patients. Lower frequency of CD16 + T cells in MB of all groups compared to their matched PB. Higher frequency of Tregs in MB of all groups compared to their matched PB. Higher T17:Treg ratio in MB vs. PB of only fertile women. Abstract: To determine usefulness of menstrual blood for assessment of differential frequency of T cell subsets, peripheral blood (PB) and menstrual blood (MB) from healthy fertile (n = 15), unexplained recurrent spontaneous abortion (URSA) women (n = 15) and unexplained infertile women (n = 8) were collected in the second day of menstrual bleeding. Frequency of T cell subsets was measured by flow cytometry. URSA and unexplained infertile patients had higher frequency of TCRαβ + CD3 + CD56 − and CD45RO + T cells as well as CD45RO + /CD45RO − ratio in PB as compared to MB. Frequency of CD3 + TCRγδ + cells in PB of unexplained infertile and MB of URSA patients were significantly lower than that in fertile group. In all groups MB contained higher percentage of CD4 + CD25 + Foxp3 + regulatory and lower percentages of CD16 + T cells compared to PB. T17 cells (CD3 + CD56 − IL-17 + ) was found to be significantly higher in MB of only fertile and unexplained infertile subjects and not URSA patients in comparison with PB. Compared to PB, only fertile women had higher T17:Treg ratio in their MB. URSA women had significantly lower MB T17 cells and T17:Treg ratio compared to those in fertile and unexplained infertile women. Based on the findings presented here, we speculate that MB has its own unique immune milieu which is not solely continuation of the immune environment of secretory endometrium. Indeed, immunophenotyping of MB immune cells could potentially be a useful tool for investigation of immunological disturbances in pregnancy-related disorders.